Teori dan Gaya Kepemimpinan Dalam Membentuk Karakter dan SDM yang Unggul - Daryoto Mulyadi Candra (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The existence of a leader in an organization/company/country is important and must exist. A leader must have good managerial skills and excel in providing examples and direction to his subordinates. Because with a good and superior theory and leadership style, you will be able to form superior character and human resources that are felt by employees and their subordinates. One of the characteristics of a leader that is needed in this modern era is example, honesty and high discipline as well as the ability to manage emotions in various matters, both in responding to the company/organization and in dealing with subordinates who are deemed to need special handling. In this research, it was found that the facts and influence of a leader in shaping the character of the people he leads cannot be separated from the upbringing of a leader who will later have superior character in facing Indonesia in the future or golden Indonesia 2045.